Determinación de la estructura horizontal de las especies del bosque de colina baja de la CC.NN. Flor de coco, distrito de Torres Causana Río Napo – Loreto Perú. 2023 - Alvarado Coral, Lucio Anderson (2024)
The research work was carried out in the low hill forest of the CC.NN. Flor de Coco del, Torres Causana district Napo River – Loreto Peru. A total of 2535 trees were recorded, 28 commercial forest species and 12 botanical families, where the families Fabaceae and Myristicaceae contain the highest number of species (seven and five species respectively), otherwise the families that contain the lowest number of species are Simaroubaceae, Sapotaceae, Vochysiaceae, Calophyllaceae, Lecythidaceae and Caryocaceae (one species each). The total volumes found are 16063.154 m3 for the entire area (2893.2 Ha). Tornillo (4162.836 m3) and Lupuna (2883.194 m3), contain the highest volume values; On the contrary, Huayruro (25,783 m3), Zapotillo (20,859 m3) and Añuje Rumo (17,402 m3) have a lower volume. It was determined that the importance value index (IVI) was: The Capinurí species (196.51%) is the most ecologically important in the low hill forest of the CC.NN. Flor de Coco, district of Torres Causana Napo River, which make up a total of 196.51% of participation in the structure of this forest. Furthermore, it can be stated that two species report little participation with less than 21% of IVI, which are represented by Lupuna (15.81%), and Quinilla (4.72%), which together add up to 20.53% respectively. It was determined that there is a difference in the horizontal structure of the commercial species of the low hill forest of the CC.NN. Flor de Coco, Torres Causana district Napo River – Loreto – Peru.